A study on the levels and withdrawal times of chloramphenicol from milk of mastitic cows medicated with chloramphenicol at therapeutic dose - Ahmet Acet; Ömer Demet; D. Ali Dinç; Bünyamin Traş; A. Levent Baş (Eurasian Journal of Veterinary Sciences)
This study was conducted to determine chloramphenicol level and its clearance time from milk cow with mastitis, which were medicated with chloramphenicol at therapeutic doses. In this experimental study, three groups that each has two Browns Swiss cows were used. Milk samples were collected and analysed in the last of 1., 2., 3., 4., 5., 6., 7., 8., 12., 24., 32., 46, hours after administration of drug. In Group I, after intramuscular enjection of 10 mg/kg chloramphenicol average drug levels were found as 24.072 mg/kg at first hour, 0.096 mg/kg at eight hour. These levels were 488.720 mg / kg at first 0.19 mg/ kg at twentyfourth hour in Group II after intra-mammar injection 2 g chloramphenicol and 784.05 mg/kg at first, 0.038 mg/kg at thirtysecond in Group III after administration of intramuscular 10 mg/kg intramammar 2 g chloramphenicol combination. No Drug residue was found in milk collected after 8 hour in Group I, 24 hour in Group II and 32 hour in Group III. The curve of chloramphenicol level was showed with a graphic against time period. As a result, chloramphenicol levels and discarding time were seen changing according to administration ways and doses.